L-Phenylalanine Supplementation Effects on Catechin Contents and Tea Quality of Fresh Assam and Chinese Green Tea Leaves - Wattanasiri, Chakree; Nusontra, Nutlada; Bunkoom, Acharavadee (Science Essence Journal, 2023)
Green tea quality can be assess by the amount of the important chemical constituents such as catechins and chlorophyll. Catechin compounds play an important role in the antioxidant capacity, especially, (-)-epicatechin gallate (ECG) and (-)-epigallocatechin gallate (EGCG), which have stronger radical-scavenging activities than other catechins. Previous research showed that L-phenylalanine is the precursor of the catechin biosynthesis. In this study, L-phenylalanine was used as a fertilizer on Assam tea (Camellia sinensis var. Assamica) and Chinese tea (Camellia sinensis var. Sinensis) for 1 month. Afterwards, the fresh tea samples were collected and their chemical composition, antioxidant capacity, chlorophyll contents, and the LAB color level were studied. The results showed that L-phenylalanine could increase the catechin concentration, especially ECG and EGCG, in fresh Assam and Chinese green tea leaves. The highest increase of ECG was found in young Chinese green tea leaves (GCN-Y) from 0.02±0.30 mg/g to 0.27±0.01 mg/g. The highest increase of EGCG was found in young Assam green tea leaves (GAS-Y) from undetected to 0.31±0.01 mg/g. The total chlorophyll contents were increased in both Assam and Chinese green tea which the highest increase was found in old Assam green tea leaves (GAS-O) from 4.80±0.07 mg/g to 7.92±0.13 mg/g. The change in the latter correlated with the LAB color level. Moreover, the results of the color change in fresh Assam green tea leaves could be observed by the naked eyes. However, the antioxidant capacity of the fresh green tea leaves has not significantly changed after supplementation with L-phenylalanine.